2018
DOI: 10.1038/s42005-017-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal topological insulators

Abstract: Topological insulators insulate in the bulk but exhibit robust conducting edge states protected by the topology of the bulk material. Here, we design a colloidal topological insulator and demonstrate experimentally the occurrence of edge states in a classical particle system. Magnetic colloidal particles travel along the edge of two distinct magnetic lattices. We drive the colloids with a uniform external magnetic field that performs a topologically non-trivial modulation loop. The loop induces closed orbits i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
(32 reference statements)
3
25
0
Order By: Relevance
“…In previous work [6], we have shown that edge transport between topologically distinct lattices occurs in the form of skipped orbits [15,16,18,17,19,20]. Like the penetrating spiral orbits shown here, both forms of edge transport are truly topological and the transport is determined and protected by topological invariants.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In previous work [6], we have shown that edge transport between topologically distinct lattices occurs in the form of skipped orbits [15,16,18,17,19,20]. Like the penetrating spiral orbits shown here, both forms of edge transport are truly topological and the transport is determined and protected by topological invariants.…”
Section: Discussionsupporting
confidence: 62%
“…In previous works we have shown how the motion of colloidal particles above periodic magnetic lattices can be of topological nature [3,4,5,6], and how the same topological concepts apply to both particle and "wave" systems [7,8,9,10,11,12,13,14]. Working with colloidal systems, as opposed to "wave" systems has however the advantage of a direct visualization of the motion and can therefore be more intuitive.…”
Section: Introductionmentioning
confidence: 98%
“…( 4 ), allows exploring the assembly and dynamics for large field amplitudes, which are currently unreachable by our experimental setup. These results, however, could be readily tested with other ferromagnetic thin films able to support larger field modulations 35 . Increasing the applied field, leads to a stronger localization of nanoparticles in the trap and simultaneously strengthens the repulsion between them.…”
Section: Resultsmentioning
confidence: 99%
“…Edge currents have also been found in models with active spinners in confinement 34 , as well as in other studies of active rotators 46 . There are also studies of colloids undergoing oscillatory motion on patterned substrates where edge motion occurs along interfaces 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of active matter frequently employ particles that undergo run-and-tumble dynamics or driven diffusion 26 . Chiral active matter consisting of circularly moving particles or spinners 26,27 is another class of active systems that can describe biological circle swimmers [26][27][28] , selfpropelled colloids 27,29,30 , active gears [31][32][33] , interacting rotators 34,35 , circularly driven particles [36][37][38][39][40] , and collections of rotating robots 41 .…”
Section: Introductionmentioning
confidence: 99%